How did the Brazilian military use to get sick before Covid-19? An analysis of the hospitalization profile of the active-duty personnel in the Brazilian Army Central Hospital from 1998 to 2018 (Research, Society and Development, 2022)
Background: The covid-19 pandemic showed how understanding the epidemiology of specific populations is extremely necessary for adequate health care. For this, it is necessary to know the health-disease profile of the military population (which differs from civilians), but free from the biases that the exceptional events of this catastrophe could generate. Aims: The study aims to characterize the temporal trend and the profile of hospitalizations of active-duty military admitted to the Brazilian Army Central Hospital from 1998 January 1st to 2018 December 31st (before Covid-19 pandemic). Methodology: Analytical cross-sectional study with non-nominal secondary data from the records of the Hospital Information System of the Brazilian Army Central Hospital. Simple linear regression (p